Pengaruh Kompetensi, Independensi, dan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Pada Karyawan Kantor Jasa Akuntansi di Kota Semarang - Aniqotunnafiah Aniqotunnafiah; Febriyantoro Aryo Putro; Endang Dwi Wahyuningsih; Dimas Adi Wicaksono; Gede Mardirta Tama (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the influence of competence, independence, and information technology on the quality of financial statements among employees of Accounting Service Offices in Semarang City. This research uses a quantitative approach with a survey method targeting employees of Accounting Service Offices in Semarang City. Data were collected through questionnaires and analyzed using multiple linear regression with the aid of SPSS software, obtaining 60 respondents. The results of the study indicate that the three independent variables, namely competence, independence, and information technology, have a positive and significant effect on the quality of financial statements. These findings confirm that improving professional competence, applying strong independence principles, and effectively utilizing information technology are important factors in producing reliable, relevant, and timely financial statements.